Identification of Immunodominant Antigens From a First-Generation Vaccine Against Cutaneous Leishmaniasis - Germanó, María José; Mackern-Oberti, Juan Pablo; Vitório, Jessica Gardone; Duarte, Mariana Costa; Pimenta, Daniel Carvalho; Sanchez, Maria Victoria; Bruna, Flavia Alejandra; Lozano, Esteban Sebastián; Fernandes, Ana Paula; Cargnelutti, Diego Esteban (Frontiers in Immunology, 2022)
Leishmaniasis is a neglected tropical disease (NTD) caused by parasites belonging to the Leishmania genus for which there is no vaccine available for human use. Thus, the aims of this study are to evaluate the immunoprotective effect of a first-generation vaccine against L. amazonensis and to identify its immunodominant antigens. BALB/c mice were inoculated with phosphate buffer sodium (PBS), total L. amazonensis antigens (TLAs), or TLA with Poly (I:C) and Montanide ISA 763. The humoral and cellular immune response was evaluated before infection. IgG, IgG1, and IgG2a were measured on serum, and IFN-γ, IL-4, and IL-10 cytokines as well as cell proliferation were measured on a splenocyte culture from vaccinated mice. Immunized mice were challenged with 104 infective parasites of L. amazonensis on the footpad. After infection, the protection provided by the vaccine was analyzed by measuring lesion size, splenic index, and parasite load on the footpad and spleen. To identify immunodominant antigens, total proteins of L. amazonensis were separated on 2D electrophoresis gel and transferred to a membrane that was incubated with serum from immunoprotected mice. The antigens recognized by the serum were analyzed through a mass spectrometric assay (LC-MS/MS-IT-TOF) to identify their protein sequence, which was subjected to bioinformatic analysis. The first-generation vaccine induced higher levels of antibodies, cytokines, and cell proliferation than the controls after the second dose. Mice vaccinated with TLA + Poly (I:C) + Montanide ISA 763 showed less footpad swelling, a lower splenic index, and a lower parasite load than the control groups (PBS and TLA). Four immunodominant proteins were identified by mass spectrometry: cytosolic tryparedoxin peroxidase, an uncharacterized protein, a kinetoplast-associated protein-like protein, and a putative heat-shock protein DNAJ. The identified proteins showed high levels of conserved sequence among species belonging to the Leishmania genus and the Trypanosomatidae family. These proteins also proved to be phylogenetically divergent to human and canine proteins. TLA + Poly (I:C) + Montanide ISA 763 could be used as a first-generation vaccine against leishmaniasis. The four proteins identified from the whole-protein vaccine could be good antigen candidates to develop a new-generation vaccine against leishmaniasis.